How do you factor ##x^6-7x^3-8##?

Like this,
##x^6-7x^3-8 -= (x^3)^2 -7(x^3) -8 -= (x^3-8)(x^3+1) -= (x^3-(2)^3)(x^3+(1)^3)##
Recall that, ##a^3+b^3=(a+b)(a^2-ab+b^2)## and ## a^3-b^3=(a-b)(a^2+ab+b^2)##
##=> (x-2)(x^2+2x+4)(x+1)(x^2-x+1)##

Posted in Uncategorized

Leave a Reply

Your email address will not be published. Required fields are marked *

You may use these HTML tags and attributes:

<a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>